Study of the Relationship Between Self-efficacy and Health-Promoting Lifestyle and Associated Factors in Nurses - Abolfazl Mohammadbeigi; Zohreh Anbari; Narges Mohammadsalehi; Aida Mahdipour; Robabeh Ahmadli; Hossein Ansari (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2016)
Background and objectives: Lifestyle is a uniqe pattern of behavioures, habits and charactristics that are exhibited by any people and is used as an indicator of physical health. The current study was conducted to investigate self-efficacy and healthy-promoting lifestyle and associated factors in nurses in Qom.